Need Analysis for Developing a Semiotic-Based Augmented Reality Media to Enhance Numeracy Literacy Among Deaf Children - Christine Wulandari Suryaningrum; Nafiah Nafiah; Asti Bhawika Adwitiya; Syahrul Mubaroq (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study aims to analyze the needs for developing a semiotic-based Augmented Reality (AR) learning medium to enhance numeracy literacy among deaf students. A qualitative descriptive method was employed through open-ended questionnaires and interviews involving teachers at Sekolah Luar Biasa Negeri Branjangan, Jember Regency, Indonesia. The findings indicate that although 50% of teachers are familiar with AR technology, all participants expressed a strong need and enthusiasm for its implementation in numeracy instruction. Teachers perceived that the visual, interactive, and semiotic features of AR can transform abstract mathematical concepts into concrete and meaningful learning experiences that align with the visual learning strengths of deaf students. The study also revealed that color, animation, and three-dimensional visualization significantly enhance students’ attention and conceptual understanding. The integration of semiotic principles—icons, indices, and symbols—into AR design enables the representation of mathematical meaning through visual signs that are easily accessible and interpretable. This approach bridges the gap between symbolic understanding and experiential learning in mathematics. The findings highlight the significant potential of AR not only as a technological innovation but also as a semiotic learning environment that supports inclusive education for students with hearing impairments. Moreover, these results provide a theoretical and practical foundation for teacher training programs on the use of AR-based technology in special education contexts.Keywords: augmented reality, deaf learners, inclusive education, numeracy literacy semiotics.AbstrakPenelitian ini bertujuan menganalisis kebutuhan pengembangan media pembelajaran Augmented Reality (AR) berbasis semiotik untuk meningkatkan literasi numerasi di kalangan siswa tuna rungu. Metode deskriptif kualitatif digunakan melalui kuesioner terbuka dan wawancara yang melibatkan guru di Sekolah Luar Biasa Negeri Branjangan, Kabupaten Jember, Indonesia. Temuan penelitian menunjukkan bahwa meskipun 50% guru familiar dengan teknologi AR, semua peserta menyatakan kebutuhan dan antusiasme yang kuat untuk menggunakan AR dalam pembelajaran numerasi. Guru merasa bahwa fitur visual, interaktif, dan semiotik AR dapat mengubah konsep matematika abstrak menjadi pengalaman konkret dan bermakna yang selaras dengan kekuatan pembelajaran visual siswa tuna rungu. Penelitian ini juga menemukan bahwa warna, animasi, dan visualisasi tiga dimensi secara signifikan meningkatkan perhatian dan pemahaman konseptual. Mengintegrasikan prinsip-prinsip semiotik ikon, indeks, dan simbol ke dalam desain AR memungkinkan representasi makna matematika melalui tanda-tanda visual yang mudah diakses dan diinterpretasikan. Pendekatan ini menjembatani kesenjangan antara pemahaman simbolik dan pengalaman dalam matematika. Temuan ini mengindikasikan adanya potensi besar untuk mengembangkan dan mengimplementasikan media AR sebagai inovasi teknologi tetapi sebagai lingkungan belajar semiotik yang mendukung pendidikan inklusif bagi siswa dengan gangguan pendengaran sekaligus menjadi dasar bagi pelatihan guru dalam pemanfaatan teknologi berbasis AR di sekolah luar biasa. Kata kunci: augmented reality, siswa tuna rungu, pendidikan inklusif, literasi numerasi, semiotik.